Problems in learning Pilipino among the Ibanag first year high school students of the Cagayan Valley Institute of Technology - Catabui, Sacrificia (Castillejo) 1927- (s.n.], 1969)
The study identified the distinct problems encountered by the Ibanag first year high school students and suggested solutions to the said problems. Identification of the learning difficulties of the Ibanag first year high school students will serve as a basis for the evaluation of their progress in the higher years of learning.